Forage Yield Fltom Ciiambal Ravines - Kaul, O. N. (Indian Forester, 1962)
Nearly three million acres of culturable land in India are affected by ravines, out of which nearly 14,00,000 acres are found in the States of Madhya Pradesh and Rajasthan alone along the Chambal river system. Mismanagement of these lands over long periods of time, coupled with the action of rain and flowing water has rendered these fertile alluvial plains completely barren and un-productive to present a devastating picture. It may be stated that these ravine lands need to be managed for the production of fuel, fodder and small timber to meet the demands of the local and outside population, which is the need of the day, rather than to reclaim them for the production of agricultural crops, at prohibitive and most un-economical costs. In the absence of any data, as to the potentialities of these ravines, for fodder production, preliminary trials to assess the forage yield production of these lands were started in 1957, at the Soil Conservation Research Demonstration and Training Centre, Kota (Rajasthan) and the results so far achieved indicate that these ravines would yield an average of 5,100 lbs. (green weight) of grass/acre after 3-4 years of simple closure.